THE ROLE OF STORYTELLING IN TEACHING CRITICAL THINKING SKILLS - Parvina Ilhomova, Khotamova (PT. Antis International Publisher, 2025)
Objective: To explore the effectiveness of storytelling as a pedagogical tool for enhancing critical thinking skills among students by fostering cognitive processes such as analysis, problem-solving, empathy, and reflection. Method: The study examines various storytelling techniques and their integration into educational practices. It evaluates how these methods encourage student engagement and facilitate an immersive learning experience conducive to developing critical thinking. Results: Storytelling was found to significantly enhance critical thinking skills by promoting deeper cognitive engagement. Students demonstrated improved analytical abilities, empathy, and problem-solving skills, highlighting storytelling’s value as a versatile educational tool. Novelty: This research underscores the unique role of storytelling in fostering critical thinking, offering educators innovative methods to integrate this approach into teaching practices for more effective learning outcomes.